Pengaruh Pengetahuan dan Sikap tentang Anemia pada Ibu dan Remaja terhadap Kecukupan Konsumsi Zat Besi - Lina Agestika; Vini Asri Pratiwi (Jurnal Akademika Baiturrahim Jambi, 2023)
Anemia in adolescent girls aged 15-17 years is one of the main health problems in developing countries, especially in Indonesia. Knowledge and attitudes of adolescents and their mothers about anemia can affect their iron consumption. This study aims to analyze the relationship between the knowledge and attitudes of students and mothers about anemia with iron consumption in female adolescent. This is a cross-sectional study with a random sampling technique. Respondents were 67 pairs of female adolescents and their mothers. Collecting data in this study by filling out a knowledge and attitude questionnaire about anemia, and iron consumption was measured by food recall 2 x 24 hours. Data analysis in this study used the chi-square test.  The results showed that adolescents with insufficient iron intake were 34.2%. 47,8% of adolescent girls and 44,8% of mothers have less knowledge about anemia. Meanwhile, the attitudes of female adolescents and mothers towards anemia were not good at 19.4% and 38.8%. Statistical analysis revealed that female adolescents with high knowledge (p-value: 0.000) and positive attitude (0.021) were more likely to consume high iron intake. Mothers' knowledge about anemia also showed the same result (p-value: 0.039), but not with their attitude (p-value = 0.969). In conclusion, female adolescents knowledge and attitudes in term of anemia are important in maintaining adequate iron intake.